Obojestranska prednost v vidnem delovnem spominu je opazna šele ob preseženi spominski kapaciteti posamezne hemisfere - Slana Ozimič, Anka (Psihološka obzorja (Ljubljana), 2019)
What are the mechanisms of visual information maintenance that underlie its highly limited capacity is a key question in visual working memory research. Previous studies emphasized the role of posterior brain regions, which enable the formation of visual representations. Their contralateral organization allows individuals to maintain more information when they are presented across both visual hemifields and are processed by both hemispheres. This phenomenon is known as bilateral advantage. Based on previous findings on bilateral advantage in visual information maintenance, the aim of our study was to assess at what working memory load can bilateral advantage be observed, and whether in the case of bilateral presentation of information participants can take full advantage of joint left and right hemisphere%s capacities. Eighteen students (13 woman) aged between 19 and 41 participated in the study and completed a change detection task, in which they were asked to recognize a change in the orientation of the objects presented to the left, right, or both visual hemifields. The results showed that the participants were able to maintain more visual information and gave quicker responses when objects were distributed across both visual hemifields, which is in line with the assumption that bilateral display facilitates the use of both hemispheres' capacities. Furthermore, the results showed that bilateral advantage occurs only when visual working memory load exceeds the capacity of the individual hemispheres. Despite significant bilateral advantage, bilateral presentation of visual information, however, does not allow the participants to utilize the full joint capacity of the two hemispheres, suggesting that the capacity of visual working memory is limited not only by the ability to form representations, but also by an additional cognitive system.
Keywords: bilateral advantage; brain; cognitive psychology; delovni spomin; kognitivna psihologija; možgani; neuropsychology; nevropsihologija; obojestranska prednost; short term memory; vidne reprezentacije; vidno-prostorski spomin; visual repersentations; visuospatial memory